Wisdom and wellbeing in polish older adults: the mediating role of forgiveness - Brudek, Paweł; Steuden, Stanisława; Kaleta, Kinga (Frontiers in Psychology, 2023)
Objectives Possible correlations between wisdom and wellbeing among older people have been extensively debated in psychology. At the same time, researchers emphasize that the effect of older adults' wisdom on their wellbeing depends on numerous mediators. A review of the literature suggests that forgiveness might be one such variable. Thus, this study aimed to investigate whether forgiveness mediated the relationship between wisdom and wellbeing in late adulthood. Method In total, 481 participants aged from 60 to 92 years (M = 68.84; SD = 6.31) were involved in the study. All older people participating in the study lived independently in their households. Four psychological instruments were used: (1) the Self-Assessed Wisdom Scale; (2) the Heartland Forgiveness Scale; (3) the Psychological Wellbeing Scale; and (4) the Satisfaction with Life Scale. Therefore, the measurement of the analyzed variables was self-reported. Results The results showed that forgiveness mediated the relationships between wisdom and wellbeing in the older population. The indirect effects demonstrated that forgiveness mediated the relationships between wisdom and wellbeing. Wisdom related to higher forgiveness (β = 0.21; p < 0.01), which, in turn, was related to a higher level of psychological (β = 0.48; p < 0.01) and subjective (β = 0.36; p < 0.01) wellbeing. Conclusion These findings suggest that forgiveness is an important element of wisdom and wellbeing. The greater the wisdom the participants showed, the stronger the tendency to forgive and the better wellbeing they reported.